2007
DOI: 10.1080/09669760701516967
|View full text |Cite
|
Sign up to set email alerts
|

Children’s access to pre‐school education in Bangladesh

Abstract: Using the Education Watch household survey database, this paper explores children's access to preschool education in Bangladesh. Participation in pre-school education has been increasing in Bangladesh at the rate of 0.6% per year and the net enrolment rate was found to be 13.4% in 2005. Enrolment of over-aged children in pre-school education made the gross enrolment ratio as high as 30.5%. However, over half of the four to five year olds at school were actually enrolled in primary school and not in pre-school.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…This was considered an important form of analysis because the country operates different models of pre-school education through various implementing bodies which are accessible to a small portion of the children. The government is, however, in the process of extending early years provision to make it available to all of pre-school aged children in the country (Government of Bangladesh 2010;Nath and Sylva 2007). Consistent with previous research, the findings reported here reveal that a very small portion of the children in this study had some experience of pre-school education before starting primary education (Nath and Sylva 2007).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This was considered an important form of analysis because the country operates different models of pre-school education through various implementing bodies which are accessible to a small portion of the children. The government is, however, in the process of extending early years provision to make it available to all of pre-school aged children in the country (Government of Bangladesh 2010;Nath and Sylva 2007). Consistent with previous research, the findings reported here reveal that a very small portion of the children in this study had some experience of pre-school education before starting primary education (Nath and Sylva 2007).…”
Section: Discussionsupporting
confidence: 85%
“…The government is, however, in the process of extending early years provision to make it available to all of pre-school aged children in the country (Government of Bangladesh 2010;Nath and Sylva 2007). Consistent with previous research, the findings reported here reveal that a very small portion of the children in this study had some experience of pre-school education before starting primary education (Nath and Sylva 2007). More specifically, the results indicate that children living in urban areas and whose parents are educated and well-off are more likely to be enrolled in a pre-school programme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with limited budgets and chronic poverty, least developed countries face a huge disadvantage with regard to providing access to preschool education for lower income families and for children in remote areas. Bangladesh, for example, is a least developed country in which disadvantaged children have low rates of access to preschool education because, evidently, no department or ministry of education has taken seriously enough the issue of preschool education at the national level (Nath & Sylva, 2007). In Cambodia, for example, where Rao and Pearson (2007) examined childcare and education policies, 80 percent of Cambodians live in rural areas, yet almost no rural children are enrolled in early childhood education.…”
Section: Introductionmentioning
confidence: 99%